Active biocatalyst for biodiesel production from spent coffee ground. (October 2018) - Sarno, Maria; Iuliano, Mariagrazia
Graphical abstract: Highlights: Ionic interaction and stability of immobilized enzyme. Very high activity on NPs support. Recycling of oil from spent coffee ground to biodiesel. Oil conversion ∼100%, FAMEs and linolenic contents in agreement with EN 14214. Abstract: Physical adsorption preserving activity and support reusability was used to directly bond lipase from Thermomyces lanuginosus on citric acid (CA) modified Fe3 O4 /Au magnetic nanoparticles. A new faster approach has been used for CA ligand exchange, which ensures an high payload of stable enzyme. The immobilized lipase was tested for the biodiesel production from spent coffee ground in a solvent free system. It retains, after 60 days, more than 90% of its initial activity. Biodiesel yield of 51.7%, after 3 h of synthesis, which increases up to ∼100% after 24 h indicating an enzymatic fast kinetic, was measured. No significant decrease, during the first three cycles of use, of the lipase activity occurs. The biodiesel presents an ester content of 98.4 ± 0.23 in agreement with the EN14214. The iodine value of 76.67 (g iodine/100 g) is in agreement with the European standard.